Storability of Different Hermetic Bags on Seed Quality Attributes of Maize in Khumaltar, Lalitpur - Bhandari, Gopal; Adhikari, Bhim Nath; Bhandari, Balram; Adhikari, Jagat Bandhu; Kaduwal, Sangita; Pokhrel, Pragya (Agronomy Journal of Nepal, 2023)
To evaluate the comparative superiority of exotic hermetic seed storage bags versus locally available bags supplemented with or without desiccants for on-farm seed storage of smallholders, an experiment was conducted in the National Seed Science and Technology Research Centre (NSSTRC) of Nepal Agricultural Research Council (NARC) from May 2017 to June 2019. Maize seed variety Manakamana-3 was allocated in 8 treatments based on storage devices with three replications in a completely randomized design (CRD). The 98% initial germinating seed was stored in eight different storage containers viz., S1, Super grain bag; S2, PICS bag; S3, Safe Grain bag; S4, 400-gauge plastic bag; S5, 400-gauge plastic double liner; S6, 400 gauge + metal bin; S7, 400 gauge + Zeolite beads; S8, 400 gauge + roasted wheat. All seed attributing data were taken in tri-monthly intervals for two and half years. In the first year, all seven treatments were found statistically at par results for germination above 85% by meeting the Nepalese maize seed standard except 400-gauze plastic bag-single liner. However, significant differences were seen in each treatment in the second year. Results on germination of storage structures with desiccants viz., 400 gauge + Zeolite beads, and 400 gauge + roasted wheat were found superior to any other storage structures such as PICS bag, Super grain bag, Safe grain bag, 400 gauge + metal bin, & 400-gauge plastic double liner. Whereas, the single liner of a 400-gauge plastic bag was found non-suitable and found vulnerable to fungal infestation in long-run storage in ambient storage conditions. Hence, it was concluded that the locally fabricated seed storage bags provided equal results to exotic hermetic bags for one season seed storage in Mid-hill, humid and sub-temperate condition of Nepal and hence, found economical modified atmospheric storage (MAS) option for small holder farmers.